1980
DOI: 10.1152/jappl.1980.49.3.516
|View full text |Cite
|
Sign up to set email alerts
|

Diphenhydramine reduces endotoxin effects on lung vascular permeability in sheep

Abstract: Because, in sheep, histamine-induced increased lung vascular permeability is prevented by diphenhydramine, we tested the effects of diphenhydramine on the sheep lung vascular response to endotoxin. We infused E. coli endotoxin (0.40-1.00 micrograms/kg) with and without diphenhydramine (3.0 mg/kg bolus + 1.5 mg . kg-1 . h-1) in the same unanesthetized sheep while measuring pulmonary arterial (Ppa) and left atrial (Pla) pressures, lung lymph flow (Qlym) and lymph (L) and plasma (P) protein concentrations. Endoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…A contributory role for histamine and NO in increased pulmonary vascular permeation during septic shock has been documented (10,34,40). In this study, we found that treatment with diphenhydramine or L-NNA significantly but partially inhibited endotoxin-induced lung vascular permeability.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A contributory role for histamine and NO in increased pulmonary vascular permeation during septic shock has been documented (10,34,40). In this study, we found that treatment with diphenhydramine or L-NNA significantly but partially inhibited endotoxin-induced lung vascular permeability.…”
Section: Discussionsupporting
confidence: 56%
“…Moreover, we have found that endotoxin administration causes superinduction of histamine H 1 receptors in cardiovascular tissues of rabbits (20,21). Earlier studies showed that blockade of histamine H 1 receptors with diphenhydramine was effective in the increase in lung vascular permeability in animal models of sepsis (10,34). Thus the hypothesis that histamine may, at least in part, mediate increased lung vascular permeability caused by endotoxemia is plausible.…”
mentioning
confidence: 80%
“…This suggests that, while both H 1 - and H 2 -receptors are involved in lung and liver injury, only H 2 -receptors contribute to kidney injury in sepsis. The involvement of histamine via H 1 -receptors in lung vascular hyperpermeability in sepsis has been documented [9, 31]. H 2 -receptors have also been shown to be involved in the recruitment of neutrophils and protein leaks in LPS-induced acute lung injury [32].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with this, the current study showed a significant increase in H 1 -receptor mRNA in lungs from CLP-induced septic mice. Histamine can affect pulmonary vascular response, lung mechanics, and pulmonary vascular permeability, effects that may be blocked by H 1 -receptor antagonism (Brigham et al, 1980). Thus, histamine may be a potentially important mediator in the pathogenesis of septic lung injury.…”
Section: Discussionmentioning
confidence: 99%